Oxygen-modulated photoresponse in nickel oxide thin films for wide band gap photodetector application - Swati Suman; Anupama Behra; Parasuraman Swaminathan (Discover Applied Sciences)
Abstract Metal oxides, due to their wide band gap, are well suited for use in photodetectors as the active light-absorbing layer. While there have been extensive studies on n-type oxides, such as tungsten oxide and zinc oxide, there is relatively little work on the use of p-type oxides, such as nickel oxide (NiO), for photodetectors. Using these p-type oxides along with n-type conducting oxides to form heterojunctions can improve the detection capabilities by efficient separation of charge carriers. In this work, the photoresponse of a p-type NiO thin film, grown by room temperature reactive magnetron sputtering from a pure nickel target onto a conducting n-type indium-doped tin oxide (ITO) substrate, is investigated. Different ratios of oxygen to argon (10/45, 15/45, and 20/45) during sputtering are investigated, and the effect of oxygen concentration on the optical properties of the NiO film is studied, which helps in modulating the photoresponse of the developed detector. The O2/Ar ratio, with a value of 15/45, is found to perform better among the three ratios. For the corresponding photodetector, the current under illumination, is found to be nearly three orders of magnitude higher than the dark current, even at a very low applied voltage of 0.1 V. The calculated responsivity (at 0.012 A/W) is found to be the best among all three values. The device also has an excellent transient current response with a rise time of 0.5 s and a decay time of 1.4 s, which is the fastest transient behavior among all three ratio-based devices. The work paves the way for using metal oxide-based heterojunctions as wide band gap photodetectors.